Participation of nurses in the care of a hemodialysis patient - Pluta, Agnieszka; Budnik-Szymoniuk, Maria; Basińska-Drozd, Halina; Sulikowska, Beata (Journal of Education, Health and Sport, 2017)
With the progress of medicine and the improvement in the quality of life, the number of patients with chronic kidney disease, including those involved in the hemodialysis program, is increasing. This method of treating renal replacement therapy is a chance for patients to prolong life, but at the same time poses the risk of many complications associated with this therapy. Nursing staff who handle the patient during hemodialysis should have the ability to correctly identify and solve problems, thus giving the patient and his family a greater sense of security. Careful observation of the patient in terms of the possibility of complications and immediate response are crucial in the care of a hemodialysis patient.